Penciptaan Sudut Literasi Fisik Sebagai Upaya Meningkatkan Pemahaman Aktivitas Fisik di Sekolah Dasar - Angga, Prayogi Dwina; Nurwahidah, Nurwahidah; Makki, Muhammad; Sari, Mega Puspita (State Islamic University of Mataram, 2024)
This community service focuses on creating a physical literacy corner as an effort to instill knowledge about the importance of physical activity and increase active lifestyle behavior. This activity was carried out at Kekait 1 State Elementary School, West Lombok Regency, West Nusa Tenggara. There are three main stages in this activity, namely the preparation, implementation, and evaluation stages. During the preparation stage, the service team coordinates with the school to analyze problems and determine solutions. Focus Group Discussion (FGD), media development, and content preparation are carried out at the service implementation stage. Then, at the end of the activity, the service team carried out a comprehensive evaluation. This activity has completed the physical literacy corner, which was developed and implemented in class 5. The books, posters, and media provided in the literacy corner will be an interesting learning resource for students. With a physical literacy corner, students have easy access to information about the importance of physical activity. With the physical literacy corner, it is hoped that SDN 1 Kekait students can continue to understand the importance of physical activity and lead a healthier and more active lifestyle.